The The Implementation of Cultural Filter in English-Indonesian Translation of Children Comic The Wizards of Mickey: The Dark Ages - Tacazely, Alrina Raras; Yuliasri, Issy; Hartono, Rudi (English Education Journal, 2019)
In translation, cultural differences become a huge obstacle for the translators to create a good translation. This study aims to explain the cultural filters in English-Indonesian translation of the children comic based on the dimensions proposed by House (2004, 2005). It also explains the functional equivalence achieved by the translation of the comic. This study is a descriptive qualitative study. In collecting the data, the researcher used transcription, table of cultural filters based on the dimensions of the cultural filters, and table of functional equivalence. The data were analyzed based on the dimensions of cultural filters in the terms of directness, orientation towards self versus orientation towards other, orientation towards content versus orientation towards addressee, explicitness versus implicitness, ad-hoc formulation versus verbal routines, and voice. The results showed that there were 310 cultural filters. Out of 310 cultural filters, 118 were explicitness versus implicitness, 85 were ad-hoc formulation versus verbal routines, 64 were orientation towards content versus orientation towards addressee, 15 were directness and orientation towards self versus orientation towards other, and 13 were cultural filter in terms of voice. Relating to the functional equivalence, 287 of them achieved functional equivalence and 23 dialogues did not achieve functional equivalence. It could be concluded that cultural filters could help the translators to overcome the problems relating to cultural differences in both source language and target language. Besides, it also helps the translation to achieve functional equivalence.